Pelaksanaan Program Tahfidzul Qur’an Berbasis Online Masa Pandemi Covid-19 - Wardah Wafiyah Mubarakah; Erni Munastiwi (State Islamic Institute of Madura, 2020)
During the Covid-19 pandemic that attacked the Indonesian state, all agencies were temporarily closed, especially educational institutions. This policy was carried out with the aim of not spreading the spread of Covid-19 among students. Even so, each agency still assigns tasks for students to do at home. This stipulation was implemented by the Taruna Al-Qur'an Putri Islamic Boarding School, which compiled an online-based tahfidz program as the duty of students while at home during this pandemic. However, in its implementation, not all santriwati perform these tasks optimally, thus making researchers want to know more about the implementation of the online-based tahfidz program. This study uses a qualitative research method with 7 respondents as research objects. The results of this study indicate that each program assigned to santriwati from the Islamic boarding school whether ziyadah, muroja'ah, and the increment of juz can be carried out properly and effectively from both the musyrifah and santriwati, although sometimes there are obstacles and obstacles in its implementation, however, not a barrier. Because every problem will and solution.